A Avaliação na sala de aula de matemática: práticas e concepções - Sampaio, Michele dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to understand the assessment practices used by teachers at a public state school in the city of Cunha, Sao Paulo. To this end, we interviewed five mathematics teachers, who answered a questionnaire with five questions. The responses were analyzed according to the rigor of phenomenological research. To understand the investigation region, that is to say, the meaning of evaluation, we proceeded to a review of studies on the subject in authors like Buriasco (2002), Pavanello (2006), Hoffmann (1994), expressive in Mathematics Education that allows us to explain the concept of prevailing interpretation in the area. The phenomenological analysis enabled the development of three categories open revealing the concept of evaluation of teachers investigated. The first shows the review As a way to measure the knowledge acquired by the student. His interpretation leads us to understand that for some teachers, the research subjects, the assessment becomes a method to ' measure ' the knowledge acquired by the student. The second category, expressed by As a way of understanding the student's behavior in class, shows that some of the interviewees understand the evaluation as a medium that reveals and appreciates the ways of the student behave in class. Finally, the third category refers to the evaluation by means of said instruments. On this subject the claim that the assessment is through instruments such that: evidence, exercise lists, among others. In summary, interviews and categories analyzed explain the ways in which the assessment reveals the concept of implicit learning the instruments used in the evaluation practices of teachers interviewed. However, the authors read, evaluation is a necessary and permanent teaching job in teaching, which must follow step by step the process of teaching and learning. It follows, ... (Complete abstract click electronic access below)

Esta pesquisa tem por objetivo compreender as práticas de avaliação utilizadas por professores de uma escola pública da rede estadual de ensino do município de Cunha, São Paulo. Para tanto, foram entrevistados cinco professores de Matemática, os quais responderam a um questionário contendo cinco questões. As respostas foram analisadas conforme o rigor da pesquisa fenomenológica. Para compreender a região de inquérito, ou seja, o sentido da avaliação procedeu-se a uma revisão dos trabalhos a respeito do tema em autores como Buriasco (2002), Pavanello (2006), Hoffmann (1994), expressivos na Educação Matemática, o que nos permite explicitar a concepção de avaliação predominante na área. A análise fenomenológica possibilitou a elaboração de três categorias abertas reveladoras da concepção de avaliação dos professores investigados. A primeira mostra a avaliação Como um modo de mensurar o conhecimento adquirido pelo aluno. Sua interpretação nos leva a compreender que, para alguns professores, sujeitos da pesquisa, a avaliação torna-se um método que permite 'medir' o conhecimento adquirido pelo aluno. A segunda categoria, expressa por Como um modo de compreender o comportamento do aluno em aula, mostra que alguns dos sujeitos entrevistados compreendem a avaliação como um meio que revela e valoriza os modos de o aluno portar-se em aula. Por fim, a terceira categoria refere-se ao Diz da avaliação por meio de instrumentos. Nesta os sujeitos afirmam que a avaliação se dá por meio de instrumentos, tais quais: provas, listas de exercícios, dentre outros. Em síntese, as entrevistas e categorias analisadas explicitam os modos pelos quais a avaliação expressa a concepção de aprendizagem implícita aos instrumentos usados na prática avaliativa dos docentes entrevistados. Porém, segundo ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Matemática - Estudo e ensino; Fenomenologia; Aprendizagem; Mathematics Study and teaching